Assessing the impact of the Dobbs v. Jackson decision on abortion attitudes by abortion identity labels: a mixed-methods longitudinal study - Xiana Bueno; Lucrecia Mena-Meléndez; Brandon L. Crawford; Ronna C. Turner; Wen-Juo Lo; Kristen N. Jozkowski (Sexual and Reproductive Health Matters, 2025)
Landmark legislative events can shift public opinion. We conducted a longitudinal survey examining abortion attitudes before and after Dobbs v. Jackson which overturned Roe v. Wade in 2022. Wave 1 (N = 1,014) was conducted in June 2022, and Wave 2 (N = 792) in October–November 2022. Using bivariate analyses, we assessed people’s attitudes towards the Dobbs decision and potential changes in abortion attitudes over time, across different abortion identity sub-groups (e.g. pro-life, pro-choice). Results indicate that people were informed about (90%) and disagreed (56%) with the decision, and did not report or experience a change in attitudes after the decision (68–73%). However, among those who did change, respondents were more inclined to endorse legal abortion after the decision (19–22%) than indicate abortion should not be legal (6–13%). Through analysing open-ended data, we found that participants more inclined to endorse legal abortion described the ruling as eroding personal rights, government intrusion, and threatening access to healthcare. Participants less inclined to endorse legal abortion indicated the ruling reinforced their belief in defending fetal rights. While not necessarily advocating outright illegality, such participants favoured stricter regulations. Notably, people who identified as “both/neither/prefer not to answer” tended to disagree with the Dobbs decision and lean towards greater endorsement of legal abortion. Uncertainty regarding (dis)agreement with the Dobbs decision was also higher among people who identified as pro-life and “both/neither/prefer not to answer” than among those who identified as pro-choice. These findings highlight important nuances that exist in abortion attitudes beyond the perceived dichotomy of the pro-life/pro-choice spectrum.